Stone Topography – Useful Tool in Monuments Restoration Process - Cihla, Michal; Kovářová, Kateřina; Malát, Richard; Valach, Jaroslav (Acta Polytechnica, 2022)
The surface of building stone on historic buildings often bears the original traces of craftsmanship processing. These are an integral part of the visual appearance of the monument and thus its value, which needs to be protected. For studying and identifying traces and subsequent reconstruction of stonemason’s tools, we use the methods of traceology and mechanoscopy. Using modern imaging techniques, we can identify the stonemason’s tool used, reconstruct the shape of its blade, and determine how it was used. The obtained results can be used in the process of monument care, especially in the process of preparation and implementation of restoration interventions on the objects, but they are also useful for completing the historical context of the monument. Our research is focused on the systematic study of the surface topography of the stone monuments in Prague. The obtained results were systematically divided according to individual historical period. As a model example of the use of the above-mentioned methods and approaches, we present the topography of stone elements and the development of stonemason’s craft in Gothic Prague. The development of the stonemason’s craft within one city in a given period can be documented on selected examples arranged chronologically in succession.